2005
DOI: 10.1080/10473289.2005.10464649
|View full text |Cite
|
Sign up to set email alerts
|

Summer and Winter Nonmethane Hydrocarbon Emissions from On-Road Motor Vehicles in the Midwestern United States

Abstract: On-road vehicle emission rates of nonmethane hydrocarbons (NMHCs) were measured in two tunnels in Milwaukee Milwaukee area with tunnel emissions showed the impact of seasonal differences in fuels and emissions on the urban atmosphere. Composition of fuel samples collected from area gas stations in both seasons was correlated with vehicle emissions; the predominant difference was increased winter emissions of lighter hydrocarbons present in winter gasoline. A chemical mass balance model was used to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 20 publications
5
45
0
Order By: Relevance
“…Additionally, the slope of the correlation between i-pentane and n-pentane (range for each season each year=1.5-2.6) (Fig. 7c) was within the range of reported emission ratios for vehicle exhaust and tunnel studies (∼2.2-3.8), liquid gasoline (1.5-3), and fuel evaporation (1.8-4.6) (Conner et al, 1995;Harley et al, 2001;Watson et al, 2001;Jobson et al, 2004;McCaughey et al, 2004;Lough et al, 2005;Velasco et al, 2007). Overall, these results suggest that a uniform mix of emissions from numerous alkane sources is observed at TF.…”
Section: Comparison With Tracers and Source Signaturessupporting
confidence: 73%
“…Additionally, the slope of the correlation between i-pentane and n-pentane (range for each season each year=1.5-2.6) (Fig. 7c) was within the range of reported emission ratios for vehicle exhaust and tunnel studies (∼2.2-3.8), liquid gasoline (1.5-3), and fuel evaporation (1.8-4.6) (Conner et al, 1995;Harley et al, 2001;Watson et al, 2001;Jobson et al, 2004;McCaughey et al, 2004;Lough et al, 2005;Velasco et al, 2007). Overall, these results suggest that a uniform mix of emissions from numerous alkane sources is observed at TF.…”
Section: Comparison With Tracers and Source Signaturessupporting
confidence: 73%
“…Daily can measurements (usually obtained at mid-day) showed that unlike other anthropogenic hydrocarbons, toluene was elevated in summer and fall as well as winter (85±5, 88±5 and 95±3 pptv, respectively), with a spring minima (56±4 pptv). White et al (2008b) examined the summer enhancement of toluene in detail, attributing it to primarily a combination of enhanced fuel evaporation of reformulated gasoline with its higher toluene content (Lough et al, 2005) and to vegetative emissions, with a minor contribution from local industrial emissions. The vegetative emissions of toluene observed by White et al (2008b) from a loblolly pine at Duke Forest were well correlated with monoterpenes.…”
Section: Aromatic Compounds -Benzene (Cmentioning
confidence: 99%
“…Recently, Schnitzhofer et al (2008) have suggested that the toluene:benzene ratio in winter should be lower than that in summer due to reduced evaporation of toluene. However, Lough et al (2005) conducted tunnel studies in Milwaukee, WI (latitude 43.11 • N, the same as TF) that show emissions of toluene are nearly constant throughout the year with mean emissions of 357±143 mg L −1 fuel in summer (largely due to evaporation) and 363±232 mg L −1 fuel in winter (largely due to incomplete combustion). Benzene emissions from mobile sources were observed to be 167±59 mg L −1 fuel in summer and 95±26 mg L −1 fuel in winter (Lough et al, 2005).…”
Section: Aromatic Compounds -Toluene:benzene Ratiomentioning
confidence: 99%
See 2 more Smart Citations